Cross-Modal Perceptual Organization in Works of Art. (August 2020) - Albertazzi, Liliana; Canal, Luisa; Micciolo, Rocco; Hachen, Iacopo
This study investigates the existence of cross-modal correspondences between a series of paintings by Kandinsky and a series of selections from Schönberg music. The experiment was conducted in two phases. In the first phase, by means of the Osgood semantic differential, the participants evaluated the perceptual characteristics first of visual stimuli (some pictures of Kandinsky's paintings, with varying perceptual characteristics and contents) and then of auditory stimuli (musical excerpts taken from the repertoire of Schönberg's piano works) relative to 11 pairs of adjectives tested on a continuous bipolar scale. In the second phase, participants were required to associate pictures and musical excerpts. The results of the semantic differential test show that certain paintings and musical excerpts were evaluated as semantically more similar, while others were evaluated as semantically more different. The results of the direct association between musical excerpts and paintings showed both attractions and repulsions among the stimuli. The overall results provide significant insights into the relationship between concrete and abstract concepts and into the process of perceptual grouping in cross-modal phenomena.